2021
DOI: 10.1186/s12935-021-02337-5
|View full text |Cite
|
Sign up to set email alerts
|

Eribulin activity in soft tissue sarcoma monolayer and three-dimensional cell line models: could the combination with other drugs improve its antitumoral effect?

Abstract: Background Eribulin has shown antitumour activity in some soft tissue sarcomas (STSs), but it has only been approved for advanced liposarcoma (LPS). Methods In this study, we evaluated the effect of eribulin on proliferation, migration and invasion capabilities in LPS, leiomyosarcoma (LMS) and fibrosarcoma (FS) models, using both monolayer (2D) and three-dimensional (3D) spheroid cell cultures. Additionally, we explored combinations of eribulin wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 60 publications
(46 reference statements)
2
3
0
Order By: Relevance
“…Eribulin was not highly effective against LMS but had a higher response rate than trabectedin and pazopanib in several, rare sarcomas. STS in the TERT ‐mutated cluster, including MLPS and SFT, had a high response rate that was consistent with the findings of previous in vitro and in vivo studies 48,50,51 . TERT ‐mutation status may be a potential, predictive biomarker for eribulin.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Eribulin was not highly effective against LMS but had a higher response rate than trabectedin and pazopanib in several, rare sarcomas. STS in the TERT ‐mutated cluster, including MLPS and SFT, had a high response rate that was consistent with the findings of previous in vitro and in vivo studies 48,50,51 . TERT ‐mutation status may be a potential, predictive biomarker for eribulin.…”
Section: Discussionsupporting
confidence: 89%
“…STS in the TERT ‐mutated cluster, including MLPS and SFT, had a high response rate that was consistent with the findings of previous in vitro and in vivo studies. 48 , 50 , 51 TERT ‐mutation status may be a potential, predictive biomarker for eribulin. In clustering analysis, STS associated with the MDM2 (amp)/ TP53 (WT)/ RB1 (WT) cluster (#6), which generally corresponds to DDLPS, showed a trend toward lower eribulin efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…The use of eribulin for LMS has not been supported because, in a subgroup analysis, there was no apparent difference between eribulin and dacarbazine (standard active drug in this pathology) in OS (12.8 months in the eribulin arm and 12.3 months in the dacarbazine arm, respectively) and PFS (2.6 months in both treatment arms) [6]. In our study, we observed that the IC 50 of eribulin for our cell lines is in the nanomolar range, as demonstrated by Hayasaka et al [27], Stehle et al [28], and by Escudero et al in a panel of STS cell lines [29]. Our LMS cell lines are more sensitive to eribulin than LPS cell lines, contrary to what has been published in several clinical trials, so we are providing new data supporting the use of eribulin also for LMS.…”
Section: Discussionsupporting
confidence: 82%
“…In this regard, Escudero and colleagues assessed the effect of eribulin (an antitumor agent approved for advanced liposarcoma treatment) on inhibiting the proliferation, migration, and invasion of LPSs and LMSs in 3D spheroid cell cultures. For the first time, they explored erilubin's action under 3D conditions in LMSs and LPSs, demonstrating an increase in the GI 50 (growth inhibitory concentration by 50%) values to a nanomolar range compared to in a 2D cellular context [54].…”
Section: Established Cancer-derived Cell Linesmentioning
confidence: 99%